2001
DOI: 10.1021/jf001192k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Molecular Species of Glycolipids in Fruit Pastes of Red Bell Pepper (Capsicum annuum L.) by High-Performance Liquid Chromatography−Mass Spectrometry

Abstract: Five major glycolipid classes (acylated steryl glucoside, steryl glucoside, monogalactosyldiacylglycerol, digalactosyldiacylglycerol, and glucocerebroside) from fruit pastes of red bell pepper were separated by silica gel column chromatography. The molecular species of each glycolipid were separated and characterized by reversed-phase high-performance liquid chromatography coupled with on-line mass spectrometry using atmospheric pressure chemical ionization. The molecular species of steryl glucoside were beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 21 publications
(31 reference statements)
6
40
0
1
Order By: Relevance
“…This chemical composition is quite close to that of the red Bell Pepper (Capsicum annuum) [26]. Edible plant glycolipids are believed to play a role in human diet as nutrients.…”
Section: Discussionsupporting
confidence: 57%
“…This chemical composition is quite close to that of the red Bell Pepper (Capsicum annuum) [26]. Edible plant glycolipids are believed to play a role in human diet as nutrients.…”
Section: Discussionsupporting
confidence: 57%
“…The general features of the 1 H and 13 C NMR spectra containing typical peaks for a b-glucoside (d H 4.94,d,J = 7.8 Hz;d C 62.9,71.8,75.5,78.8,78.9,105.9), an amide (d C 176.0, d H 8.58d), and several other oxygenated (d C 70.8, 72.7(2), 76.2) or N-substituted (d C 52.0) carbon atoms besides a di-substituted double bond (d C 131.0, 131.2; d H 5.52 m) and long-chain aliphatic moieties (d C 14.6-35.9) suggest the possible identification of this molecule as a cerebroside. The molecular formula deduced from the above Mass and NMR spectral data was already reported for a constituent of Capsicum annuum L. by Yamauchi et al (2001) and of several Euphorbia species by Cateni et al (2003aCateni et al ( , b, 2008. But our sample (ASE-1) showed typical peaks for the allylic carbons of a 'trans' olefin rather than 'cis' (d C 33-34 ppm and not 27-28 ppm).…”
Section: Statistical Analysessupporting
confidence: 57%
“…Yamauchi et al 9 previously reported the detection of free phytosterols and phytosterol glucoside derivatives in chili pepper by performing consecutive prefractionations before analysis. During this study, a single generic sample preparation protocol was applied to extract all of the compounds reported in this paper.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…The fatty acid moieties that were found to be part of the galactosyldiacylglycerol lipids consisted of C18:3, C18:2, C18:1, C18:0, C16:3, C16:2, C16:1, and C16:0, which corresponds with previous findings. 9 Relative abundances were calculated for the monogalactosyldiacylglycerol and digalactosyldiacylglycerol families with the acetate adducts obtained in negative APCI mode. Monogalactosyldiacylglycerol (18:3/18:3), digalactosyldiacylglycerol (18:3/18:3), digalactosyldiacylglycerol (18:3/16:0), and digalactosyldiacylglycerol (18:3/18:0) were the most abundant galactosyl diacylglycerol lipids present in the chili pepper accessions, as previously found.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%